2022
DOI: 10.3390/cancers14040961
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Lung Cancer: Mechanisms and Associations with Histological Subtypes, Molecular Alterations, and Major Epidemiological Factors

Abstract: Lung cancer is the major leading cause of cancer-related mortality worldwide. Multiple epigenetic factors—in particular, DNA methylation—have been associated with the development of lung cancer. In this review, we summarize the current knowledge on DNA methylation alterations in lung tumorigenesis, as well as their associations with different histological subtypes, common cancer driver gene mutations (e.g., KRAS, EGFR, and TP53), and major epidemiological risk factors (e.g., sex, smoking status, race/ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 192 publications
(243 reference statements)
0
21
0
Order By: Relevance
“…For example, several PRMT inhibitors are undergoing phase 1/2 clinical trials [30]. Furthermore, certain methylation markers, such as DAL-1, EPHB6, HS3ST2, TMEM88 and MGMT, specifically associated with lung cancer progression and metastasis, were found to have increased methylation levels [31]. Also, previous research revealed that methylation of the BRCA1 promoter in peripheral blood DNA was linked to a 3.5-fold increased risk (95% CI, 1.4-10.5) of developing breast cancer before the age of 40 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several PRMT inhibitors are undergoing phase 1/2 clinical trials [30]. Furthermore, certain methylation markers, such as DAL-1, EPHB6, HS3ST2, TMEM88 and MGMT, specifically associated with lung cancer progression and metastasis, were found to have increased methylation levels [31]. Also, previous research revealed that methylation of the BRCA1 promoter in peripheral blood DNA was linked to a 3.5-fold increased risk (95% CI, 1.4-10.5) of developing breast cancer before the age of 40 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in methylation patterns have been observed in the subtypes of lung cancer, mutation status of cancer-driven genes, and various epidemiological factors ( 22 ). Therefore, the identification of methylation sites of cancer-specific genes may be helpful to molecular classification and disease stratification ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the study by Ai et al, triptolide induces the expression of endogenous miR-15a and inhibits the Hippo-yes-associated protein (Hippo-YAP)/TAZ pathway, leading to the cytotoxicity, senescence and apoptosis of ovarian GCs ( Ai et al, 2018 ). Additionally, epigenetic therapy is a promising approach for the treatment of cancers ( Matthews et al, 2021 ; Xu et al, 2021 ; Brown et al, 2022 ; Hoang and Landi 2022 ). Since DNA methylation plays an important role in the formation of primordial germ cells, epigenetic therapy, e.g., DNMT inhibitor-based (such as decitabine) therapies, may hamper oocyte differentiation and development and thus induce POI ( Yang et al, 2019 ).…”
Section: Epigenetic Mechanisms Regulating the Occurrence And Developm...mentioning
confidence: 99%